LI I 6708A BLEND IN THE SPECTRA OF STRONGLY MAGNETIC STAR HD166473 - Shavrina, A. V.; Khalack, V.; Glagolevskij, Y.; Lyashko, D.; Landstreet, J.; Leone, F.; Polosukhina, N. S.; Giarrusso, M. (Одеські астрономічні публікації, 2013)
The analysis of Li I 6708 Ǻ blend in the spectra of HD166473 was performed for 6 rotational phases distributed over the whole rotational period (P 9.5 years). The magnetic ﬁeld model has been constructed based on the polarimetric measurements from Mathys et al. (2007). For each observed phase the modulus of the magnetic ﬁeld has also been estimated from the modeling of Fe II 6147 Ǻ, 6149 Ǻ and Pr III 6706.7 Ǻ line profiles taking into account Zeeman magnetic splitting and the angle α between the magnetic axis and the line of sight. Our measurements of the surface magnetic field agree rather well with the results of Mathys et al. (2007). The lithium abundance in each phase was obtained from the fit of the observed Li I 6708 Ǻ line with the synthetic profile calculated assuming Paschen-Back splitting for the characteristics of magnetic field estimated from the analysis of Pr III 6706.7 Ǻ line profile. We have also estimated the abundances of Ce II, Sm II, and Nd II, whose lines contribute to the Li 6708 Ǻ blend.